Effects of Off-Axis Elliptical Training on Reducing Pain and Improving Knee Function in Individuals With Patellofemoral Pain. Issue 6 (November 2015) - Tsai, Liang-Ching; Lee, Song Joo; Yang, Aaron J.; Ren, Yupeng; Press, Joel M.; Zhang, Li-Qun
Abstract : Objective: To examine whether an off-axis elliptical training program reduces pain and improves knee function in individuals with patellofemoral pain (PFP). Design: Controlled laboratory study, pretest–posttest. Setting: University rehabilitation center. Participants: Twelve adult subjects with PFP. Interventions: Subjects with PFP completed an exercise program consisting of 18 sessions of lower extremity off-axis training using a custom-made elliptical trainer that allows frontal plane sliding and transverse plane pivoting of the footplates. Main Outcome Measures: Changes in knee pain and function posttraining and 6 weeks after training were evaluated using the Knee Injury and Osteoarthritis Outcome Score (KOOS) and International Knee Documentation Committee (IKDC) scores. Lower extremity off-axis control was assessed by pivoting and sliding instability, calculated as the root mean square (RMS) of the footplate pivoting angle and sliding distance during elliptical exercise. Subjects' single-leg hop distance and proprioception in detecting lower extremity pivoting motion were also evaluated. Results: Subjects reported significantly greater KOOS and IKDC scores (increased by 12-18 points) and hop distance (increased by 0.2 m) after training. A significant decrease in the pivoting and sliding RMS was also observed after training. Additionally, subjects with PFP demonstrated improved pivoting proprioception when tested under a minimum weight–bearing position. Conclusions: An off-axis elliptical training program was effective in enhancing lower extremity neuromuscular control on the frontal and transverse planes, reducing pain, and improving knee function in persons with PFP. Clinical Relevance: This study provides a novel intervention approach to enhance the control of the frontal and transverse plane motions of the lower extremities during functional weight-bearing activities. This novel off-axis elliptical training may be incorporated with other common treatment options currently available for PFP to augment the effects of musculoskeletal rehabilitation for the PFP population.